Effects of Sleep Reactivity on Sleep Macro-Structure, Orderliness, and Cortisol After Stress: A Preliminary Study in Healthy Young Adults - Feng YZ; Chen JT; Hu ZY; Liu GX; Zhou YS; Zhang P; Su AX; Yang S; Zhang YM; Wei RM; Chen GH (Nature and Science of Sleep, 2023)
Yi-Zhou Feng,1,* Jun-Tao Chen,1,2,* Zhen-Yu Hu,1,* Gao-Xia Liu,1 Yu-Shun Zhou,1 Ping Zhang,1 Ai-Xi Su,1 Shuai Yang,1 Yue-Ming Zhang,1 Ru-Meng Wei,1 Gui-Hai Chen1 1Department of Neurology (Sleep Disorders), Chaohu Hospital of Anhui Medical University, Hefei, Anhui, 238000, People’s Republic of China; 2Department of Neurology, Shangyu People’s Hospital of Shaoxing, Shaoxing, Zhejiang, 312000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gui-Hai Chen, Department of Neurology (Sleep Disorders), Chaohu Hospital of Anhui Medical University, Hefei, Anhui, 238000, People’s Republic of China, Tel +86-13956094425, Email doctorcgh@163.comPurpose: To investigate changes and links of stress and high sleep reactivity (H-SR) on the macro-structure and orderliness of sleep and cortisol levels in good sleepers (GS).Patients and Methods: Sixty-two GS (18– 40 years old) were recruited, with 32 in the stress group and 30 in the control group. Each group was further divided into H-SR and low SR subgroups based on the Ford Insomnia Response to Stress Test. All participants completed two nights of polysomnography in a sleep laboratory. Before conducting polysomnography on the second night, the stress group completed the Trier Social Stress Test and saliva was collected.Results: The duration of NREM sleep stages 1, 2 (N1, N2) and rapid eye movement sleep (REM) decreased, and the values of approximate entropy, sample entropy, fuzzy entropy, and multiscale entropy increased under stress and SR effects. Stress increased rapid eye movement density, and H-SR increased cortisol reactivity.Conclusion: Stress can damage the sleep and increase cortisol release in GS, especially those with H-SR. N1, N2 and REM sleep are more easily affected, while NREM sleep stage 3 sleep is relatively stable.Keywords: cortisol, entropy, insomnia, polysomnography, sleep reactivity, stress